1995
DOI: 10.1007/bf00192112
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of basement membrane molecules by salivary adenoid cystic carcinoma cells: an immunofluorescence and confocal microscopic study

Abstract: The biosynthesis of basement membrane molecules and fibronectin was studied in vitro in the two different human cell systems (ACC2 and ACC3) established from adenoid cystic carcinomas (ACC) of the salivary gland using immunofluorescence and confocal microscopy. When cells were attached and spread on dishes, fine granular immunofluorescence for type IV collagen, laminin, heparan sulphate proteoglycan, entactin, and fibronectin first appeared diffusely in the cytoplasm, and then changed in aggregation of coarse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
0
4

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(87 citation statements)
references
References 27 publications
2
81
0
4
Order By: Relevance
“…38 In vitro, ACC3 cell line also produces basement membrane molecules, including type IV collagen, laminin, heparan sulfate proteoglycan, and fibronectin. 6,28 It has been shown that E-cad methylation density of CpG sites increases when tumor cells are cultured on coated basement membrane molecules. 26 Excessive production of extracellular molecules in adenoid cystic carcinoma might thus be associated with a high incidence of E-cad gene methylation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 In vitro, ACC3 cell line also produces basement membrane molecules, including type IV collagen, laminin, heparan sulfate proteoglycan, and fibronectin. 6,28 It has been shown that E-cad methylation density of CpG sites increases when tumor cells are cultured on coated basement membrane molecules. 26 Excessive production of extracellular molecules in adenoid cystic carcinoma might thus be associated with a high incidence of E-cad gene methylation.…”
Section: Discussionmentioning
confidence: 99%
“…For the in vitro experiments, the ACC3 cell line, originally derived from a patient of adenoid cystic carcinoma arising from the parotid gland, was used. 28 Cultured tumor cells were maintained in RPMI-1640 medium (Gibco BRL, Rockville, MD, USA) supplemented with 10% fetal bovine serum (Gibco BRL), 1% L-glutamine, 50 mg/ml streptomycin, and 50 IU/ml penicillin, and incubated at 371C under a humidified atmosphere containing 5% CO 2 .…”
Section: Tissue Samples Of Surgical Cases and Cell Culturementioning
confidence: 99%
“…22 Salivary gland adenoid cystic carcinoma (ACC) cell systems (lines), ACC2 and ACC3, were established from ACCs of the palatal minor salivary gland and parotid gland, respectively, 23 and ACCM was subcloned from ACC2 cells as a clone with highly metastatic potential. 22 SCC cells were cultured in Dulbecco's modified Eagle medium (DMEM; Gibco, Invitrogen, Carlsbad, CA, USA) and ACC cells were cultivated in RPMI 1640 medium (Gibco), both of which contained 10% fetal bovine serum (Gibco), 50 mg/ml streptomycin, and 50 IU/ml penicillin (Gibco) (DMEMþ , RPMIþ ).…”
Section: Materials and Methods Clinical Samplesmentioning
confidence: 99%
“…The molecular alterations that underlie the tumor development and progression are poorly understood. To determine if the high level of Sox4 gene expression plays a role in the pathogenesis of ACC, we used RNA silencing (RNAi) technology to inhibit Sox4 expression in the ACC-derived cell line ACC3 (Cheng et al, 1995) and assayed parameters of cell growth and apoptosis. We also identified relevant target genes that are differentially expressed in the Sox4 knockdown ACC3 using oligonucleotide microarray technology.…”
Section: Introductionmentioning
confidence: 99%